"It's not too bad" - The Lived Experience of Energy Saving Practices of Low-Income Older and Frail People. (September 2017) - Willand, Nicola; Maller, Cecily; Ridley, Ian
Abstract: Drawing on evidence from a mixed methods retrofit intervention trial of the homes of low-income, older and frail people in Victoria, Australia, this study explored practices of heating and keeping warm in terms of equity and health. In most homes, heating restrictions led to inadequate indoor temperatures. Adaptation practices increased householder resilience, however, some technical responses presented safety risks. Low-cost retrofits did not eliminate underheating and had little effect on householder practices. The study highlights that a promotion of no-cost energy saving activities acknowledges the adaptive capacity of individuals. However, failure to address material and technical conditions and the vulnerability of older people may lead to unintended health risks.